Pengaruh Aspek Lingkungan terhadap Profitabilitas Perusahaan Peserta PROPER di Bursa Efek Indonesia - Fitri , Rafi Latifah; Suhendro , Saring (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The issue of achieving corporate profitability often conflicts with environmental responsibilities, particularly in the mining, basic materials, and industrial sectors that heavily rely on natural resource exploitation. The imbalance between economic interests and environmental sustainability raises questions about how environmental performance, environmental costs, and environmental disclosure influence corporate profitability. This study aims to obtain empirical evidence regarding the effect of environmental performance, environmental costs, and environmental disclosure on the profitability of companies in the mining, basic materials, and industrial sectors that participate in the PROPER program and are listed on the Indonesia Stock Exchange for the period 2019–2023. This research employs a quantitative approach using multiple linear regression analysis.The data used are secondary data in the form of annual financial reports, sustainability reports, and PROPER ratings, collected through documentation methods. The sample consists of 31 companies selected using purposive sampling based on specific criteria. The results show that environmental performance and environmental disclosure have a positive and significant effect on profitability. Conversely, environmental costs have a negative and significant effect on profitability. The implications of these findings suggest that companies should incorporate environmental aspects into their sustainable business strategies. Good environmental performance and disclosure can enhance a company’s legitimacy and profitability, while inefficiently managed environmental costs may pose a financial burden that reduces financial performance.